From Qumran Caves to Swiss Vaults: Unprovenanced Dead Sea Scrolls-Like Fragments and Transformative Travels - Justnes, Årstein (Dead Sea discoveries, 2024)
When first announced, many of the post-2002 Dead Sea Scrolls-like fragments were depicted as experienced travelers having moved over long distances. Some of Martin Schøyen’s fragments had allegedly been to Bethlehem, Lebanon, and Zurich before they eventually came to Norway. According to Weston W. Fields, the so-called Butterfly fragment—William Kando’s fabled Genesis scroll—was first sent to Germany before it “made its way to the vault [in Switzerland]” in 1965 or 1966. Other fragments had traveled from Bethlehem to Beirut, from Beirut to Cyprus, and from Cyprus to Zurich, but no one seemed to know exactly how. In most cases the fragments “appeared,” “found/made their way,” “turned up,” “saw the light,” or “surfaced” in the fulness of time. More recently, the Israel Antiquities Authority’s (IAA) sensational (and unprovenanced) “Ishmael Papyrus” was even said to have “come to the awareness of epigraphists” 50 years after an unnamed Montana woman hung it on the wall in her living room. The fragment’s last trip from Montana to the IAA’s Dead Sea Scrolls lab managed to transform the living room decoration into a Dead Sea Scroll fragment of great scientific interest. In this article, I analyze some of these itineraries—the routes between the ideal starting point (Khirbet Qumran or, more specifically, Qumran Cave 4) and the ideal laundering point (Zurich, a Swiss vault, the IAA’s Dead Sea Scrolls lab)—and discuss their function. My main interest is to show how stories of long-distance mobility transform the status of fake and unprovenanced fragments.